The Influence of Organizational Justice on Managers’ Decision-Making - Hussein, Khalil Anwar (European Scientific Journal, ESJ, 2023)
The process of decision-making plays a substantial role in the life of each organization, because the results affect all employees at all levels. Therefore, making-decision is considered the most significant and intricate managerial task. In addition, it might become more problematic when executives work with people across cultures, since individuals from varied cultural backgrounds understanding matters in a different way. Thus, decisions that are formed by senior managers are most imperative and impactful to the way an organization works. However, senior managers’ decisions may have negative effects. In addition, organizational fairness is complex and refers to the fair and right treatment of persons within an organization. Thus, persons would like fairness as it recompences them for their input. Poor organizational justice is a considerable reason of negative response from staffs, because they have a strong sense of inequality. Often, ethical dilemmas result from intricate circumstances and discrepancy of values within organizations.